2018
DOI: 10.1136/bmjopen-2018-022569
|View full text |Cite
|
Sign up to set email alerts
|

Association of workplace social capital with psychological distress: results from a longitudinal multilevel analysis of the J-HOPE Study

Abstract: ObjectivesWorkplace social capital (WSC) is increasingly recognised as a social contextual determinant of workers’ mental health, but longitudinal data are sparse. We aimed to evaluate the impact of changes in unit-level WSC on psychological distress among Japanese employees using a prospective multilevel repeated-measures design.Participants and study designWe conducted a 2-year prospective cohort study with 1,944 men and 786 women aged 18–65 years. Participants worked at two manufacturing worksites in Japan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…The reason may be that the location of the musculoskeletal pain was integrated in the analysis. The risk factor of NP has been reported to be psychological stress, 20,27,28 which was influenced by WSC 15,19 . In contrast, the risk factor of low back pain and wrist pain has been reported to be ergonomic factors, rather than psychological stress 28 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason may be that the location of the musculoskeletal pain was integrated in the analysis. The risk factor of NP has been reported to be psychological stress, 20,27,28 which was influenced by WSC 15,19 . In contrast, the risk factor of low back pain and wrist pain has been reported to be ergonomic factors, rather than psychological stress 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Psychological stress could be a probable explanation for the association between WSC and presence of NP. Low WSC refers to a lack of support, trust, and information from members within the same workgroup, 29 which deteriorates psychological stress 15,19 . Additionally, one study has reported that psychological stress increased muscle tension in the neck 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations